Impact of training dairy farm personnel on milking routine compliance, udder health, and milk quality - Zelmar Rodriguez; Mario Lopez-Benavides; Marianna B. Gentilini; Pamela L. Ruegg (Journal of Dairy Science)
ABSTRACT: Among various farm procedures, an appropriate milking routine is crucial for reducing mastitis and enhancing milk safety and quality. However, inadequate compliance with milking routines remains a primary factor contributing to variability of milk quality among herds. Training farm workers is essential for ensuring compliance with milking routines, which directly affects milk quality and udder health. In this study, we aimed to assess the impact of a training session on dairy farm workers' understanding of the milking routine, behavioral changes during milking, and subsequent effects on milk quality and udder health. Farm workers (n = 112) from 16 commercial dairy farms in Michigan and Ohio participated in the project. The training session was delivered using an active learning approach prioritizing group discussions, and focused on the pathogenesis, identification, and risk factors for mastitis, as well as the rationale and importance of each step in the milking routine. Pre- and post-training evaluations were conducted to measure changes in knowledge, parlor evaluations were performed to determine behavioral changes, and data from clinical mastitis cases and bulk tank SCC were used to estimate udder health and milk quality. Segmented and linear mixed regression analyses were used to assess the impact of the training intervention. Participants were mostly milking technicians (61.1%) with 70% of them having less than 1 yr of experience and a median tenure in their jobs of 9 mo. Knowledge of the milking routine increased from 49.3% to 67.6% of correct answers after training. Based on parlor evaluations, the premilking disinfectant contact time increased by 9 s per cow. The percentage of milkings with inadequate preparation time decreased from 69% (before training) to 48% (after training). The proportion of insufficient teat coverage during postmilking disinfection decreased from 9.8% (77 out of 782) before training to 5.9% (34 out of 572) after training. We observed a significant increase in clinical mastitis cases during the immediate week after the training. Additionally, the upward trend in bulk tank SCC was halted. Our results suggest an improvement in overall mastitis identification and milk quality, underscoring the importance of targeted training programs for farm workers in improving milking routine compliance, enhancing milk quality, and promoting better udder health.